Fintech, foreign bank presence and inclusive finance in Africa: Using a quantile regression approach - Iddrisu, K.; Abor, J.Y.; Banyen, K.T. (Cogent Economics & Finance, 2022)
Africa is one of the continents with the least inclusive finance. However, with increasing use of mobile phones for financial services or financial technology (Fintech), there are improved opportunities to ‘bank the unbanked”. Also, there is a significant increase in both the presence of foreign banks and Fintech usage. Hence, we examine the moderating role of foreign bank presence on the fintech-inclusive finance nexus over the period 2000–2018. The results show that foreign bank presence does not directly affect inclusive finance but increases the link between Fintech and inclusive finance. We recommend that African countries need to provide a conducive environment, improving the use of Fintech.
Research Article
Keywords: Fintech; Inclusive finance; Quantile regression